Study of butterfly as indicator for environmental condition at uitm reserve forest, Negeri Sembilan / Azizul Hakim Mohd Yaacob - Mohd Yaacob, Azizul Hakim (Faculty of Applied Sciences, 2016)
Butterflies are an important group of taxa that serve as pollinators, food source and herbivores in an ecosystem. Butterflies is a group of taxa that well studied. Many research related to butterflies are carried out. This study is carried out at UiTM Forest Reserve, Negeri Sembilan located at Kuala Pilah district. The study duration is two months that is from early of September to end of October 2015. The aim of this study is to record the composition and diversity of butterflies at UiTM Forest Reserve. A total of 200 individuals were caught during sample collection and the most family obtained at is Nyamphalidae (42%). Meanwhile the least was Papillionoidiea (2%). The Shannon Weiner-index (H’=3.92) indicates that high diversity of butterflies in studied area. The evenness index (E=0.86) shows decreasing from the past study. As for the richness index (R= 17.55) shows rich species of butterflies at UiTM Forest Reserve. The high richness and diversity of butterflies indicates that it is important to continuously maintain the biodiversity of UiTM Forest Reserve, thus further study or conservation program could be done.